Kewenangan Komisi Kepolisian Nasional dalam Mewujudkan Tata Kelola Kepolisian Yang Baik - Awaluddin, Awaluddin (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
This research aims to analyze on how the authority implementation by National Police Commission in the pursuit of manifesting good governance of police in Indonesia. This research is a normative research. The data collection method is by library researches, document studies, law acts, interview with member of the House of Representative of Indonesia, interview with National Police Commission, and interview with the Imparsial Jakarta. The data processing method is qualitative. The result of the research shows that the authority implementation by National Police Commission has not worked according to the society’s expectation. Since the authority owned by National Police Commission is too simple for a national commission that help President. Likewise, it is too weak for a commission which expected to run the supervisory function toward the performance of Indonesian Police.